Comment on “Contrast Between Chinese and Western Cultural Values and Its Effects on English Learning in China” - Rui Gao (Trans/Form/Ação)
Commented article: ZHANG, F. H. Contrast Between Chinese and Western Cultural Values and Its Effects on English Learning in China. Trans/Form/Ação: revista de filosofia da Unesp, v. 47, n. 4, “Eastern thought”, e0240062, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14621.